(untitled) (REMUNOM, 2026)
Firefighting operations in confined environments impose high physiological demands on military firefighters, constituting a significant risk to physical integrity. This study analyzed the physiological effects on 121 military firefighters during controlled exposure in a Fire Development Simulator (SDI). Pre- and post-exposure parameters were evaluated: blood pressure, heart rate, oxygen saturation, compressed air consumption, and fluid loss, using Pearson correlation analysis. Results revealed strong positive correlation (r = 0.82; p < 0.001) between systolic and diastolic blood pressure variations; moderate to strong correlation (r = 0.67; p < 0.01) between heart rate and air consumption; and strong negative correlation (r = -0.78; p < 0.001) between oxygen saturation and air consumption. Average fluid loss was -1.00 kg (± 0.40 kg) in younger quartiles, with lower deficit (-0.86 kg) in the oldest quartile. Compressed air consumption emerges as a sensitive marker of physiological load, surpassing isolated variables, recommending the implementation of individualized hydration protocols and air consumption monitoring as preventive operational strategies.